2010
DOI: 10.1590/s0004-282x2010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Emergency EEG: study of survival

Abstract: Objective: To determine the survival rate according to the main findings of emergency electroencephalography (EEGs) of patients treated in a tertiary hospital. Method: In this prospective study, the findings of consecutive emergency EEGs performed on inpatients in Hospital de Base in São José do Rio Preto, Brazil were correlated with survival utilizing KaplanMeyer survival curves. results: A total of 681 patients with an average age of 42 years old (1 day to 96 years) were evaluated, of which 406 were male. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The utility of acute EEG recordings was 100% in subjects with a referral diagnosis of SE [3]. In addition to the present evidence on the usefulness of acute EEG availability in early seizure detection and patient management, EEG findings could serve as a prognostic tool for subjects presenting with neurological and non-neurological emergencies [41-43]. It is worth noting that a single EEG with complete generalized suppression in comatose survivors after cardiac arrest indicates no possibility of recovery in the level of consciousness [44].…”
Section: Introductionmentioning
confidence: 90%
“…The utility of acute EEG recordings was 100% in subjects with a referral diagnosis of SE [3]. In addition to the present evidence on the usefulness of acute EEG availability in early seizure detection and patient management, EEG findings could serve as a prognostic tool for subjects presenting with neurological and non-neurological emergencies [41-43]. It is worth noting that a single EEG with complete generalized suppression in comatose survivors after cardiac arrest indicates no possibility of recovery in the level of consciousness [44].…”
Section: Introductionmentioning
confidence: 90%
“…Thus, most EEG records have been done in CA with therapeutic hypothermia in humans. Recent studies showed that bispectral index (<40, a calculated summary of raw EEG data including frequency and amplitude) [ 53 , 54 ], burst suppression (a quantitative EGG parameter) [ 55 , 56 ], periodic discharges (commonly recognized patterns of abnormal EEG) [ 57 , 58 ], epileptiform discharges (an uncommon EEG pattern including periodic spike, sharp and slow wave complex and more common in people with epilepsy) [ 59 ], stimulus-induced rhythmic periodic, or ictal discharges (a spectrum of stimulation-induced EEG pattern) [ 60 ] in the EEG records after successful resuscitation with non-therapeutic hypothermia may indicate poor prognosis. In addition, a non-reactive EEG [ 61 , 62 ] may predict poor prognosis in patients without therapeutic hypothermia, while rhythmic delta activity may indicate better prognosis [ 55 , 58 ] after CA [ 63 ].…”
Section: Electrophysiologic Monitoring Of Brain Injury After Cardimentioning
confidence: 99%
“…Among a series of patients with GPEDs, including post-hypoxic myoclonic encephalopathy, prion diseases, and encephalitis, approximately 60% died after 2 months; there was a 50% mortality rate for patients with status epilepticus, PLEDs, or continuous delta activity commonly related to underlying advanced liver disease [62].…”
Section: Periodic Dischargesmentioning
confidence: 99%